MANUSIA DAN PENDIDIKAN DALAM PERSPEKTIF AL-ATTAS - Baharuddin AbdRahman (Sekolah Tinggi Agama Islam Indonesia Jakarta, 2018)
This research is a type of library research, trying to explain al-Attas’ conception of man and education. The results of the study found that: (1) man is not a creature that evolved from animals, and therefore